Case Report: Simultaneous mucoid degeneration of the ACL and PCL in a 62-year-old man: an under-recognized diagnostic pitfall - Shin, Kyun-Ho; Jang, Il-Tae; Han, Seung-Beom (Frontiers in Surgery, 2025)
Mucoid degeneration of the cruciate ligaments is an uncommon and often under-recognized cause of chronic knee pain and motion limitation. We report the case of a 62-year-old man with an eight-year history of discomfort, progressive flexion contracture, and restricted range of motion in the right knee. Two prior arthroscopies performed elsewhere failed to identify the cause. Magnetic resonance imaging using a 1.5-Tesla scanner with 3-mm slice thickness demonstrated diffuse, increased intraligamentous signal with intact fibers in both the anterior and posterior cruciate ligaments, consistent with the “celery stalk” sign. Arthroscopy through standard anterolateral and anteromedial portals revealed hypertrophic, yellowish ligament tissue in both cruciates. Approximately 50% of the bulk of each ligament was resected with preservation of the remaining intact fibers to maintain stability. Histologic examination confirmed mucoid degeneration without inflammatory infiltration. At six months postoperatively, the patient achieved full extension, improved flexion to 130°, and complete resolution of pain, without clinical instability. This case emphasizes the importance of considering simultaneous ACL and PCL mucoid degeneration as a potential diagnosis in patients with refractory knee stiffness when common intra-articular pathologies have been excluded.